A new species of the weevil genus Larinus Dejean from Turkey and Syria (Coleoptera: Curculionidae: Lixinae) - Gülteki̇n, Levent (Zootaxa, 2006)
Larinus perrinae sp. n. is described from southeastern Turkey and Syria based on material from J. Desbrochers’ and M. Pic’s collections. Lectotype of L. lejeunei Capiomont is designated. Larinus perrinae is closely related to L. lejeunei but, differing in the elongated body, pattern of pubescence and shape of aedeagus.